Use of a controlled subdermal radio frequency thermistor for treating the aging neck: Consensus recommendations. (17th November 2017) - Kinney, Brian M.; Andriessen, Anneke; DiBernardo, Barry E.; Bloom, Jason; Branson, Dennis F.; Gentile, Richard D.; Goldberg, David J.; Lorenc, Paul Z.; Nestor, Mark; Wu, Douglas
ABSTRACT: Introduction : A new temperature-controlled device has been used as a percutaneous radio frequency probe to treat lax submental and other facial areas. It has significant advantages over other esthetic devices as it provides the dual benefit of fat lipolysis and skin tightening. Our goal here is to present consensus recommendations for treating the aging neck.Methods : A panel of 11 expert physicians convened in Dallas, Texas, on October 15, 2016 to arrive at a consensus on the best current practice for submental skin tightening and contour improvement. Prior to the meeting, a comprehensive review of the literature was performed and a survey was sent to esthetic dermatologists and plastic surgeons who were queried about various aspects of neck rejuvenation.Results : The literature search revealed 10 different technologies for neck rejuvenation evaluated in double-blind ( n = 2) and single-blind ( n = 1) clinical trials and other clinical evaluations ( n = 21). The survey was sent via an email to 1248 individuals and was completed by 92 respondents. Review of the data and discussion by meeting attendees generated eight consensus recommendations.Discussion : Subdermal monopolar radio frequency represents an effective means for disrupting fat volume and skin tightening of the face, neck, and jawline. For suitable patients, this treatment can be used to achieve significant esthetic improvements.